A genome-wide survey of the secondary metabolite biosynthesis genes in the wheat pathogen Parastagonospora nodorum - Chooi, Y.; Muria-González, Mariano Jordi; Solomon, P. (2014)
The model pathogen Parastagonospora nodorum is a necrotroph and the causal agent of the wheat disease Septoria nodorum blotch (SNB). The sequenced P. nodorum genome has revealed that the fungus harbours a large number of secondary metabolite genes. Secondary metabolites are known to play important roles in the virulence of plant pathogens, but limited knowledge is available about the SM repertoire of this wheat pathogen. Here, we review the secondary metabolites that have been isolated from P. nodorum and related species of the same genus and provide an in-depth genome-wide overview of the secondary metabolite gene clusters encoded in the P. nodorum genome. The secondary metabolite gene survey reveals that P. nodorum is capable of producing a diverse range of small molecules and exciting prospects exist for discovery of novel virulence factors and bioactive molecules. © 2014 © 2014 The Author(s). Published by Taylor & Francis.